It seems that some the work is already here, but I'd be glad to!! So for #3 which is 9x^2+15x, we can factor out both a 3 and an x (3x) so we know that 3x * 3x =9x^2 and 3x * 5 = 15x so once we take the 3x out of the equation, we are left with 3x(3x+5) and that's as far as you can factor.
For #4, we see that the common factor is 10m because 10m * 2n = 20mn and 10m * 3 = 30m so once we take 10m out of the original, it becomes 10m(2n-3)
For #5, this one the common factor is 4xy because 4xy * 2xy=8x^2y^2 and 4xy*x= 4x^2y and 4xy*3=12xy so once we take the 4xy out of the equation, it becomes 4xy(2xy-x-3)
Hope this helps!
Emily wanted to exchange her 300 US Dollars for Canadian Dollars.
The exchange rate for it was 1.25 Canadian Dollars for 1 US Dollar.
This means that 1 US Dollar = 1.25 Canadian Dollars.
So if we were to follow this pattern,
2 US Dollars = 2 × 1.25 = 2.5 Canadian Dollars
3 US Dollars = 3 × 1.25 = 3.75 Canadian Dollars
4 US Dollars = 4 × 1.25 = 5 Canadian Dollars
So for 300 US Dollars, we'll need to multiply 300 by 1.25.
300 US Dollars = 300 × 1.25 = 375 Canadian Dollars.
Hope it helps. :)
Answer:
It is not direct variation
Step-by-step explanation:
y/7 = 2/x
y = 7×2/x
y = 14/x
And
y = k/x
k = 14 which is the constant of proportionality
: y ∞ 1/x
This is inverse variation
Answer: The net change would be -2.
Step-by-step explanation: The upward change of elevator is represented by positive sign while the downward change represented by negative sign.
Given, First the elevator goes up 15 floors, change = + 15, Then it goes 9 floors down, change = -9, Then it goes 11 floors up,Change = + 11, Finally, it goes 19 floor down, Change = - 19 So, the net change = sum of total changes = 15 - 9 + 11 - 19 = -2
your welcome!
Answer:
x = 12
Step-by-step explanation:
Angles in a triangle add up to equal 180 degrees
Hence, 10x - 11 + 3x - 2 + 3x + 1 = 180
( note that we just created an equation that we can use to solve for x )
we now solve for x using the equation we created
10x - 11 + 3x - 2 + 3x + 1 = 180
step 1 combine like terms
10 + 3x + 3x = 16x
- 11 - 2 + 1 = -12
we now have 180 = 16x - 12
step 2 add 12 to each side
- 12 + 12 cancels out
180 + 12 = 192
we now have 192 = 16x
step 3 divide each side by 16
16x / 16 = x
192 / 16 = 12
we're left with x = 12